Optimalisasi Administrasi Perjanjian Kerja Sama Antar-Daerah dalam Mendukung Kelancaran Misi Dagang Provinsi Kalimantan Tengah dan Jawa Timur - Wulan Maizahra; Achmad Hairudin; Agus Satrya Wibowo; Wahyu Febri Eka Susanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Equitable regional development remains a major challenge in Indonesia, partly due to weak administration in inter-regional cooperation. This community service activity aims to optimize inter-regional cooperation agreement administration to support the trade mission between Central Kalimantan and East Java Provinces through the MBKM independent internship program. A participatory approach was employed, involving document management, correspondence filing, presentation preparation, and SME accompaniment. Results indicate that orderly and structured administration improved inter-agency coordination efficiency and supported the trade mission's success, which recorded transactions exceeding IDR 2.08 trillion. This program proved mutually beneficial for students and government agencies in supporting effective and accountable inter-regional cooperation.